2020
DOI: 10.3389/fonc.2020.528957
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of HPV-Associated Head and Neck Carcinomas: Recent Data and Perspectives for the Development of Specific Tumor Markers

Abstract: A significant subset of carcinomas developed in the head and neck (H&NCs) are associated with specific human papillomaviruses (HPV) genotypes. In particular, 40–60% of oropharyngeal carcinoma cases are linked to HPV. Epidemiological studies have demonstrated that HPV oral infections are predominantly sexually transmitted and are more frequent among men (10–18%) than women (3.6–8.8%). Although there is a large diversity of HPV genotypes associated with H&NCs, HPV16 lineage represents 83% of the reported cases. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 87 publications
0
13
0
4
Order By: Relevance
“…46 By analyzing the immune infiltrate in HNC, studies demonstrated that HPV-positive cancers had greater CD8+ T cell infiltrate and PD-L1 expression than HPV-negative tumors. 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…46 By analyzing the immune infiltrate in HNC, studies demonstrated that HPV-positive cancers had greater CD8+ T cell infiltrate and PD-L1 expression than HPV-negative tumors. 47 , 48 …”
Section: Resultsmentioning
confidence: 99%
“…In regard to genetic differences, HPV-positive tumors are characterized by recurrent mutations of PTEN, TRAF3 (TNF receptor-associated factor 3), and PIK3CA and focal amplification of E2F1, while HPV-negative tumors demonstrate a high rate of TP53 mutations and abrogation of the G1/S checkpoint via CDKN2A/B deletion and/or CCND1 amplification. 47 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the comprehensive genomic landscape in HPV-positive HNSCC is remarkably different from smoking-related HNSCC ( 32 34 ). In general, HPV-positive HNSCCs exhibited a relatively low mutational burden (2.28 mutations per Mb vs. 4.83 mutations per Mb in HPV-negative cases) ( 32 ), a high proliferative index, a frequent alteration in the PIK3CA pathway, compared to HPV-negative HNSCCs ( 35 ). A current study reported that the most frequent mutation exhibited in an OPSCC cohort with 948 subjects was TP53 (33%), followed by PIK3CA (17%) and KMT2D (10.6%); and TP53 was more commonly mutated in the HPV-negative group (mutation rate: 49% vs. 10%, P < 0.0005) ( 36 ).…”
Section: Hpv and Opsccmentioning
confidence: 99%
“…Various studies have been carried out to develop the examination designs. The method of examination, the molecular targets, and the biological sources used were considered in those studies [11,106,107].…”
Section: Dental Calculus: Novel Promising Biosource For Hpv-induced Oral Cancer Studymentioning
confidence: 99%